Using a virtual classroom in the Practicum: Innovations and enhanced practices - Bonadeo, Flavia S. (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article intends to communicate some of the activities developed in a Practicum context in an English Teacher Education programme. It describes and assesses some didactic choices aimed at promoting reflection, collaboration and dialogue, such as forums, collaborative writing and triangulation in assessment. Besides, it proposes that virtual classrooms may maximise the potential of these practices.